MEMBENTUK KECERDASAN SPIRITUAL PADA ANAK USIA DINI MELALUI LINGKUNGAN KELUARGA DENGAN PENDEKATAN DEEP LEARNING - pratiwi, graha; Poniman, Poniman (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
This study aims to examine how the formation of spiritual intelligence (SQ) in early childhood can be optimized through the family environment using the deep learning approach as an adaptive and in-depth learning model. The deep learning approach in this context is interpreted as an intensive and layered learning process, involving emotional interactions, spiritual experiences, and repetition in the family that supports the internalization of spiritual values ??in depth in children. The research method used is qualitative with data collection through observation, interviews, and literature studies. The results of the study indicate that a family environment rich in spiritual interactions and emotional guidance can form the foundation of children's spiritual intelligence effectively. The active role of parents in creating meaningful spiritual experiences, providing examples of religious behavior, and building an empathetic learning atmosphere is key to supporting the deep learning process in children. In addition, nutritional factors and stimulation since the womb also contribute to children's readiness to receive and process spiritual learning. This study recommends the application of a deep learning approach in the development of spiritual intelligence in early childhood by strengthening the role of the family as the main environment for spiritual learning. In conclusion, the integration of the deep learning approach with the family environment can improve the quality of spiritual intelligence formation systematically and sustainably.